Solvent-free anticorrosive paint and preparation method thereof

Through the composite technology of modified bamboo fiber and bentonite, the problem of structural instability of epoxy solvent-free paint when temperature and pressure changes is solved, and the high stability and long life of the coating film are achieved.

CN119708957APending Publication Date: 2025-03-28SHANGHAI ZHENGOU IND
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411962067.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Epoxy solvent-free paint is prone to cracking during use, especially when temperature and pressure change, the coating film is difficult to maintain its structural stability, affecting its service life.

Method used

Using the composite technology of modified bamboo fibers and bentonite, the alkali treatment is performed using sodium hydroxide solution during the preparation of modified bamboo fibers, and cellulose nanofibers are added to the modified liquid to enhance the bonding strength and interface compatibility of bamboo fibers. At the same time, bentonite is added to increase the adhesion and cohesion of the coating.

Benefits of technology

It significantly improves the structural stability of solvent-free anticorrosion coatings when temperature and pressure changes, reduces the adhesion loss rate of the coating film, and extends the service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005217419670000091
    Figure BDA0005217419670000091
  • Figure BDA0005217419670000101
    Figure BDA0005217419670000101
Patent Text Reader

Abstract

The invention relates to the technical field of solvent-free coatings, and particularly discloses a solvent-free anticorrosive coating and a preparation method thereof. The solvent-free anticorrosive paint is composed of a component A and a curing agent in a weight ratio of (3-5): 1, and the component A is prepared from the following raw materials in parts by weight: 70-80 parts of epoxy resin; 15 to 25 parts of a reactive diluent; 1-5 parts of a dispersant; 18 to 20 parts of pigment; 20 to 30 parts of filler; 0.5 to 1 part of bentonite; 1-3 parts of modified bamboo fiber; the preparation method comprises the following steps: stirring the epoxy resin at 300-700r / min, then adding the reactive diluent, the dispersant, the pigment, the filler, the bentonite and the modified bamboo fiber in the stirring process, stirring for 15-20min at 1000-1200r / min after the addition is completed, and then grinding to obtain the component A; the component A and the curing agent are stirred and mixed according to the use proportion. After being applied, the solvent-free anti-corrosion coating disclosed by the invention can keep relatively excellent structural stability when being subjected to temperature and pressure changes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of solvent-free coatings, and more specifically, to a solvent-free anti-corrosion coating and a preparation method thereof. Background Art

[0002] Solvent-free coatings refer to coatings that use no or almost no solvents in the formulation and production process. The characteristics of this type of coating include environmental protection, safety and excellent physical properties. Among them, solvent-free epoxy liquid anti-corrosion paint is a high-solid, room-temperature curing (hardening) solvent-free epoxy anti-corrosion coating. It has the advantages of oil resistance, chemical resistance, wear resistance, impact resistance, easy cleaning, etc. It has strong adhesion to the substrate and is easy to construct. It can be made into coatings of different thicknesses according to user needs. In recent years, it has been widely used in construction, chemical industry, machinery, electronics and other fields.

[0003] Solvent-free epoxy anti-corrosion coatings are mainly composed of raw materials such as epoxy resin, curing agent, pigment, and additives. Among them, epoxy resin is the main film-forming substance, which provides strength and chemical resistance to the coating; the curing agent plays a role of cross-linking reaction in the coating to form a strong coating; the pigment is used to provide the required color and increase the physical strength of the coating; additives include dispersants, stabilizers, etc., which are used to improve the performance and stability of the coating. Since the epoxy resin molecular structure contains a large number of polar groups such as hydroxyl and ether groups, the adhesion of solvent-free epoxy coatings to the substrate is very strong, especially in humid environments. It can also maintain excellent adhesion. In addition, the coating formed after the solvent-free epoxy coating is cured has physical properties such as high hardness, good wear resistance, stamping resistance, and scrub resistance Regarding the above-mentioned related technologies, the inventors believe that due to the high hardness and viscosity of epoxy solvent-free paint, it is easy to crack during use. Especially when subjected to temperature and pressure changes, the coating film formed by the epoxy solvent-free paint is difficult to maintain structural stability, which will have an adverse effect on the overall service life.

[0004] Therefore, it is urgent to propose a solution to solve the above technical problems. Summary of the invention

[0005] In order to enable the solvent-free coating to maintain relatively excellent structural stability when subjected to temperature and pressure changes after application, the present application provides a solvent-free anti-corrosion coating and a preparation method thereof.

[0006] In the first aspect, the present application provides a solvent-free anti-corrosion coating, which adopts the following technical solution: A solvent-free anti-corrosion coating, comprising a component A and a curing agent in a weight ratio of (3-5):1, wherein the component A is made of raw materials including the following parts by weight: Epoxy resin 70-80 parts; Active diluent 15-25 parts; Dispersant 1-5 parts; Pigment 18-20 parts; 20-30 parts of filler; 0.5-1 part of bentonite; 1-3 parts of modified bamboo fiber; The modified bamboo fiber is prepared by the following steps: S1, prepare 2-3 mol / L sodium hydroxide solution, take bamboo fiber raw material and sodium hydroxide solution at (1.4-1.8) g: 1 mL and mix them for 8-10 hours, then take out the bamboo fiber, wash it with deionized water and dry it, to obtain pretreated bamboo fiber; S2, taking anhydrous ethanol, a silane coupling agent and water in a weight ratio of (35-40):(3-5):1 to mix to obtain a treatment liquid, and then adding cellulose nanofibers to the treatment liquid, wherein the weight ratio of cellulose nanofibers to the treatment liquid is 1:(10-12), and mixing to obtain a modified liquid; S3, spray the modified liquid onto the surface of the pretreated bamboo fiber, the spraying amount of the modified liquid is 40-60g / m 2 , and after drying, modified bamboo fiber is obtained.

[0007] By adopting the above technical scheme, in the preparation of modified bamboo fiber, the bamboo fiber raw material is first treated with alkali with sodium hydroxide solution, which can effectively remove most of the hemicellulose, pectin and part of the lignin and wax on the surface of the bamboo fiber raw material, significantly increase the roughness of the surface of the bamboo fiber raw material, and bring about an improvement in compressive strength; then the modified liquid containing cellulose nanofibers is sprayed on the surface of the pretreated bamboo fiber, which can not only modify the surface defects of the pretreated bamboo fiber, but also make the modified bamboo fiber show strong bonding strength and interface compatibility; the modified bamboo fiber is applied to the solvent-free anti-corrosion coating, which can improve the overall structural stability of the coating when it is subjected to temperature and pressure changes. The addition of bentonite can increase the adhesion of the coating, enable the coating to better adhere to the surface of the substrate, thereby improving the adhesion of the coating, and bringing about an improvement in the cohesion of the coating, so that the temperature and pressure resistance of the solvent-free anti-corrosion coating is also improved. At the same time, when the modified bamboo fiber and bentonite are mixed and applied in solvent-free anti-corrosion coatings, the two can play an excellent compounding and synergistic role with each other. Through the networking adhesion of the modified bamboo fiber and bentonite, it can bring structural reinforcement effect in the mixing system of the solvent-free anti-corrosion coating, and show excellent resistance to temperature and pressure changes, thereby ensuring that the solvent-free anti-corrosion coating can maintain relatively excellent structural stability during the application process.

[0008] Preferably, the diameter of the bamboo fiber raw material is 10-50 μm, and the length is 1-5 mm; the diameter of the cellulose nanofiber is 10-20 nm, and the length is 80-100 nm.

[0009] By adopting the above technical scheme, in the preparation of modified bamboo fiber, after the bamboo fiber raw material of the above specifications is pretreated, the cellulose nanofibers of the above specifications in the modified liquid can form a stable interface bond with the pretreated bamboo fiber, so that the corresponding effect brought by the obtained modified bamboo fiber after application in the solvent-free anti-corrosion coating is better, and the structural stability of the solvent-free anti-corrosion coating is stronger when it is subjected to temperature and pressure changes after application.

[0010] Preferably, the weight ratio of the bentonite to the modified bamboo fiber is 0.35:1.

[0011] By adopting the above technical scheme, when bentonite and modified bamboo fiber in the above weight ratio are mixed and used, the web adhesion between them is relatively uniform and stable, and they can show strong bonding with other raw materials in the solvent-free anti-corrosion coating. When subjected to changes in temperature and pressure, they can exert relatively excellent and stable corresponding effects, thereby making the solvent-free anti-corrosion coating have better structural stability during the application process.

[0012] Preferably, 2-3 parts by weight of a functional additive are added to the raw materials of component A, and the functional additive is obtained by mixing sepiolite powder and lauric acid, heating them, and then drying them, and the weight ratio of sepiolite powder to lauric acid is 1:(1.6-2).

[0013] By adopting the above technical scheme, the microscopic layered structure of sepiolite powder in the coating can enhance the toughness of the coating structure, and sepiolite powder is a hydrated magnesium-rich silicate clay mineral, which can also improve the thermal insulation performance and enhance the temperature change resistance of the coating structure; and when lauric acid and sepiolite powder are mixed and heated to obtain a functional additive, the sepiolite powder is doped in the form of flakes in the gel formed by lauric acid, and the layered structure of the sepiolite powder is covered by the gel network molecules to form a dense sponge structure, so that the structural stability of the final solvent-free anti-corrosion coating will be significantly improved when the temperature and pressure changes during the application process.

[0014] Preferably, the weight ratio of the sepiolite powder to lauric acid is 1:1.8.

[0015] By adopting the above technical scheme, when the above-mentioned weights of sepiolite powder and lauric acid are mixed to prepare the functional additive for use, the two can form a relatively uniform and stable combination with each other, and can show strong compatibility with other raw materials of solvent-free anti-corrosion coatings, thereby making the corresponding effect brought about by the addition and use of the functional additive better.

[0016] Preferably, the reactive diluent is one or a combination of allyl glycidyl ether, phenyl glycidyl ether, butyl glycidyl ether, ethylene glycol bisglycidyl ether and resorcinol bisglycidyl ether.

[0017] By adopting the above technical scheme, the active diluent can significantly reduce the viscosity of the coating, making the coating easier to apply; and can cross-link with the resin molecules through polar interactions, hydrogen bonds and van der Waals forces to form a strong network colloidal structure, thereby preventing the coating from stratification, skinning and cessation of flow, and improving the stability of the coating; it can also improve the fluidity of the coating, making the coating smoother, and reducing the problems of bubbles and shrinkage holes on the surface of the coating, thereby improving the coating effect and quality; and the above-mentioned types of active diluents are all suitable for the application of solvent-free anti-corrosion coatings, and can stably exert the above-mentioned effects, thereby ensuring that the formed coating film has a high quality.

[0018] Preferably, the filler is one or a combination of calcium carbonate, talc powder, wollastonite powder, mica powder, graphite powder and alumina powder.

[0019] By adopting the above technical solution, fillers can not only reduce costs, but also improve other properties of the coating, such as enhancing the consistency of the coating, preventing the sedimentation of pigments and fillers, and improving the fluidity, leveling, and gloss of the coating. The above types of fillers can be used in combination according to actual needs, and can all play their own excellent characteristics.

[0020] Preferably, the curing agent is alicyclic amine resin Baxxodur EC330.

[0021] By adopting the above technical scheme, the alicyclic amine resin can ensure the rapid curing of the coating, with a high cross-linking density, and can ensure that the coating film after film formation has excellent performance, and can effectively improve the heat resistance and service life of the coating.

[0022] Preferably, the weight ratio of component A to curing agent is 4:1.

[0023] By adopting the above technical solution, the ratio of component A to the curing agent directly affects the performance of the cured product, including hardness, strength, toughness, chemical corrosion resistance, etc., and the component A and the curing agent in the above weight ratio, after being combined, can make the coating film formed by the solvent-free anti-corrosion coating have stable and excellent quality.

[0024] In a second aspect, the present application provides a method for preparing a solvent-free anti-corrosion coating, using the following technical solution: A method for preparing a solvent-free anticorrosive coating comprises the following steps: (1) preparing raw materials including epoxy resin, reactive diluent, dispersant, pigment, filler, bentonite, modified bamboo fiber and curing agent according to a proportion; (2) stirring the epoxy resin in step (1) at 300-700 r / min, then adding an active diluent, a dispersant, a pigment, a filler, bentonite and a modified bamboo fiber during the stirring process, stirring at 1000-1200 r / min for 15-20 min after the addition is completed, and then grinding to obtain component A; (3) Component A and the curing agent are stirred and mixed according to the usage ratio to obtain a solvent-free anti-corrosion coating.

[0025] By adopting the above technical scheme, the above preparation method is simple to operate, and the raw materials are added and mixed in an orderly manner, which is beneficial to quality control during the production process. In addition, the raw materials can fully cooperate with each other and play excellent corresponding roles, thereby obtaining a solvent-free anti-corrosion coating with excellent quality and stability, which is also beneficial to large-scale industrial production as a whole.

[0026] In summary, this application has the following beneficial effects: 1. Since the modified bamboo fiber prepared by special modification is used in the present application and compounded with bentonite for application in the solvent-free anti-corrosion coating, it can bring about a more significant structural enhancement effect and show excellent resistance to temperature and pressure changes, thereby ensuring the excellent structural stability of the solvent-free anti-corrosion coating during the application process; 2. The present application uses a functional additive obtained by heating a mixture of lauric acid and sepiolite powder, and utilizes the thermal regulation and pressure adaptive regulation brought by the functional additive itself, so that the structural stability of the coating film exhibited by the final solvent-free anti-corrosion coating when it is subjected to temperature and pressure changes during the application process can be significantly improved. DETAILED DESCRIPTION

[0027] The present application is further described in detail below in combination with preparation examples, embodiments and comparative examples.

[0028] Unless otherwise specified, the raw materials used in the preparation examples, embodiments and comparative examples of the present application are commercially available: The epoxy resin was purchased from Dow's low-viscosity bisphenol F liquid epoxy resin DER354 354LV; The dispersant was purchased from DISPERBYK BYK-2009; The pigment is titanium dioxide; Bentonite was purchased from Walter Organic Bentonite BP-205B; Sepiolite powder was purchased from Shijiazhuang Tourmaline Mineral Products Co., Ltd. with a specification of 325 mesh.

[0029] Preparation examples of raw materials and / or intermediates Preparation Example 1 A modified bamboo fiber is prepared by the following steps: S1, prepare 2.5 mol / L sodium hydroxide solution, take bamboo fiber raw material and sodium hydroxide solution at 1.6g:1mL and mix them for 9h, then take out bamboo fiber, wash and dry it with deionized water to obtain pretreated bamboo fiber; S2, taking anhydrous ethanol, silane coupling agent and water in a weight ratio of 37.5:4:1 to mix to obtain a treatment liquid, and then adding cellulose nanofibers to the treatment liquid, wherein the weight ratio of cellulose nanofibers to the treatment liquid is 1:11, and mixing to obtain a modified liquid; S3, spraying the modified liquid onto the surface of the pretreated bamboo fiber, and the spraying amount of the modified liquid is 50g / m 2 , and after drying, modified bamboo fiber is obtained.

[0030] Note: In the above operation, the diameter of the bamboo fiber raw material is 30 μm and the length is 3 mm; the diameter of the cellulose nanofiber is 15 nm and the length is 90 nm.

[0031] Preparation Example 2 A modified bamboo fiber, which is different from Preparation Example 1 in that it is prepared by the following steps: S1, prepare 2 mol / L sodium hydroxide solution, take bamboo fiber raw material and sodium hydroxide solution at 1.4g:1mL and mix them for 8h, then take out bamboo fiber, wash and dry it with deionized water to obtain pretreated bamboo fiber; S2, taking anhydrous ethanol, a silane coupling agent and water in a weight ratio of 35:3:1 and mixing them to obtain a treatment liquid, and then adding cellulose nanofibers to the treatment liquid, wherein the weight ratio of the cellulose nanofibers to the treatment liquid is 1:10, and mixing to obtain a modified liquid; S3, spray the modified liquid onto the surface of the pretreated bamboo fiber, the spraying amount of the modified liquid is 40g / m 2 , and after drying, modified bamboo fiber is obtained.

[0032] Preparation Example 3 A modified bamboo fiber, which is different from Preparation Example 1 in that it is prepared by the following steps: S1, prepare 3 mol / L sodium hydroxide solution, take bamboo fiber raw material and sodium hydroxide solution at 1.8g:1mL and mix them for 10 hours, then take out bamboo fiber, wash and dry it with deionized water to obtain pretreated bamboo fiber; S2, taking anhydrous ethanol, a silane coupling agent and water in a weight ratio of 40:5:1 and mixing them to obtain a treatment liquid, and then adding cellulose nanofibers to the treatment liquid, wherein the weight ratio of the cellulose nanofibers to the treatment liquid is 1:12, and mixing to obtain a modified liquid; S3, spray the modified liquid onto the surface of the pretreated bamboo fiber, the spraying amount of the modified liquid is 60g / m 2 , and after drying, modified bamboo fiber is obtained.

[0033] Preparation Example 4 A modified bamboo fiber is different from the one in Preparation Example 1 in that the diameter of the bamboo fiber raw material is 10 μm and the length is 1 mm; the diameter of the cellulose nanofiber is 10 nm and the length is 80 nm.

[0034] Preparation Example 5 A modified bamboo fiber is different from the preparation example 1 in that the diameter of the bamboo fiber raw material is 50 μm and the length is 5 mm; the diameter of the cellulose nanofiber is 20 nm and the length is 100 nm. Example

[0035] Example 1 A solvent-free anti-corrosion coating is composed of a component A and a curing agent in a weight ratio of 4:1. The raw materials of the component A and their corresponding weights are shown in Table 1. The solvent-free anti-corrosion coating is prepared by the following steps: (1) preparing raw materials including epoxy resin, reactive diluent, dispersant, pigment, filler, bentonite, modified bamboo fiber and curing agent according to a proportion; (2) stirring the epoxy resin in step (1) at 500 r / min, then adding an active diluent, a dispersant, a pigment, a filler, bentonite and a modified bamboo fiber during the stirring process, stirring at 1100 r / min for 17.5 min after the addition, and then grinding to 30 μm to obtain component A; (3) Component A and the curing agent are stirred and mixed according to the usage ratio to obtain a solvent-free anti-corrosion coating.

[0036] Note: In the above operation, the modified bamboo fiber is obtained from Preparation Example 1; the curing agent is the alicyclic amine resin Baxxodur EC330; the active diluent is propylene glycidyl ether; and the filler is calcium carbonate with a specification of 325 mesh.

[0037] Example 2 A solvent-free anti-corrosion coating, which is different from Example 1 in that step (2) is specifically configured as follows: the epoxy resin in step (1) is stirred at 700 r / min, and then an active diluent, a dispersant, a pigment, a filler, bentonite and a modified bamboo fiber are added during the stirring process; after the addition is completed, the mixture is stirred at 1000 r / min for 20 minutes, and then ground to 30 μm to obtain component A.

[0038] Example 3 A solvent-free anti-corrosion coating, which is different from Example 1 in that step (2) is specifically configured as follows: the epoxy resin in step (1) is stirred at 300 r / min, and then an active diluent, a dispersant, a pigment, a filler, bentonite and a modified bamboo fiber are added during the stirring process; after the addition is completed, the mixture is stirred at 1200 r / min for 15 min, and then ground to 30 μm to obtain component A.

[0039] Embodiment 4-5 A solvent-free anti-corrosion coating, which is different from Example 1 in that the raw materials of component A and their corresponding weights are shown in Table 1.

[0040] Table 1 Raw materials and weight portions of component A in Examples 1, 4-5 (kg / portion) raw material Example 1 Example 4 Example 5 Epoxy resin 75 70 80 Active diluent 20 15 25 Dispersants 3 1 5 pigment 19 18 20 filler 25 20 30 Bentonite 0.75 0.5 1 Modified bamboo fiber 2 1 3 Example 6 A solvent-free anti-corrosion coating, which is different from Example 1 in that the weight ratio of component A to the curing agent is 3:1.

[0041] Example 7 A solvent-free anti-corrosion coating, which is different from Example 1 in that the weight ratio of component A to the curing agent is 5:1.

[0042] Example 8 A solvent-free anti-corrosion coating, which is different from Example 1 in that 2.5 parts by weight of a functional additive are also added to the raw materials of component A, and the functional additive is obtained by mixing sepiolite powder and lauric acid, heating at 60° C. for 5 minutes, and then drying, wherein the weight ratio of sepiolite powder to lauric acid is 1:1.8, and the functional additive is added together with the modified bamboo fiber in step (2).

[0043] Example 9 A solvent-free anti-corrosion coating, which is different from Example 8 in that the weight portion of the functional additive added is 2 parts.

[0044] Example 10 A solvent-free anti-corrosion coating, which is different from Example 8 in that the weight parts of the functional additive added is 3 parts.

[0045] Embodiment 11 A solvent-free anti-corrosion coating, which is different from Example 8 in that the weight ratio of sepiolite powder to lauric acid is 1:1.6.

[0046] Example 12 A solvent-free anti-corrosion coating, which is different from Example 8 in that the weight ratio of sepiolite powder to lauric acid is 1:2.

[0047] Example 13 A solvent-free anti-corrosion coating, which is different from Example 8 in that the functional additive is sepiolite powder.

[0048] Embodiment 14 A solvent-free anti-corrosion coating, which is different from Example 8 in that the functional additive is lauric acid.

[0049] Embodiment 15 A solvent-free anti-corrosion coating is different from Example 1 in that the total amount of bentonite and modified bamboo fiber remains unchanged, and the weight ratio of the two is adjusted to 0.35:1.

[0050] Example 16 A solvent-free anti-corrosion coating, which is different from Example 1 in that the modified bamboo fiber is obtained from Preparation Example 2.

[0051] Embodiment 17 A solvent-free anti-corrosion coating, which is different from Example 1 in that the modified bamboo fiber is obtained from Preparation Example 3.

[0052] Embodiment 18 A solvent-free anti-corrosion coating, which is different from Example 1 in that the modified bamboo fiber is obtained from Preparation Example 4.

[0053] Embodiment 19 A solvent-free anti-corrosion coating, which is different from Example 1 in that the modified bamboo fiber is obtained from Preparation Example 5.

[0054] Comparative Example Comparative Example 1 A solvent-free anti-corrosion coating, which is different from Example 1 in that bentonite is not used in the raw materials.

[0055] Comparative Example 2 A solvent-free anti-corrosion coating, which is different from Example 1 in that modified bamboo fiber is not used in the raw materials.

[0056] Comparative Example 3 A solvent-free anti-corrosion coating, which is different from Example 1 in that bentonite and modified bamboo fiber are not used in the raw materials.

[0057] Comparative Example 4 A solvent-free anti-corrosion coating, which is different from Example 1 in that the modified bamboo fiber and other materials are replaced by bamboo fiber raw materials.

[0058] Comparative Example 5 A solvent-free anti-corrosion coating, which is different from Example 1 in that bentonite is not used in the raw materials, and the modified bamboo fiber is replaced by bamboo fiber raw materials.

[0059] Performance test samples: The solvent-free anti-corrosion coating obtained in Examples 1-19 was used as test sample 1-19, and the solvent-free anti-corrosion coating obtained in Comparative Examples 1-5 was used as control sample 1-5.

[0060] Test method: The solvent-free anti-corrosion coating was tested according to the requirements of the standard HG / T 5177-2017 "Solvent-free anti-corrosion coating" in terms of adhesion (pull-off method) / MPa, and the obtained adhesion strength was recorded as the initial value M; At the same time, after the solvent-free anti-corrosion coating is made into a coating film according to the requirements of the adhesion (pull-off method) / MPa in the standard HG / T 5177-2017 "Solvent-free Anti-corrosion Coating", it is first placed in a high and low temperature alternating test box, with an initial temperature of 25°C, first heated to 80°C at 3°C / min, then cooled to -5°C at 1.5°C / min, and then heated to 25°C at 2°C / min, recorded as 1 cycle, and continued for 20 cycles; then a hydraulic pressure tester is used to apply a variable pressure of 0.2-1.5MPa to the surface of the coating film, each change cycle is 60s, and after completing 10 change cycles; finally, the solvent-free anti-corrosion coating is tested according to the requirements of the adhesion (pull-off method) / MPa in the standard HG / T 5177-2017 "Solvent-free Anti-corrosion Coating", and the obtained adhesion strength is recorded as the experimental value N; Calculate the adhesion strength loss rate, adhesion strength loss rate = (MN) / M, the greater the adhesion strength loss rate, the worse the structural stability of the solvent-free anti-corrosion coating when subjected to temperature and pressure changes after application. After completing the above tests on test samples 1-19 and control samples 1-5 in turn, the corresponding results are recorded in Table 2.

[0061] Table 2 Test results of test samples 1-19 and control samples 1-5 Combining Examples 1-5 and Comparative Examples 1-3 and Table 2, it can be seen that the use of specially modified modified bamboo fibers and compounding with bentonite for use in solvent-free anticorrosive coatings can significantly improve the structural stability exhibited when subjected to temperature and pressure changes during the application process, and after the above test, the obtained adhesion strength loss rate is also significantly reduced; and if any one of the modified bamboo fibers and bentonite is used alone, although the adhesion strength loss rate obtained by the test can be reduced, the amplitude is limited, and the sum of the corresponding effects brought by the use of each of the two alone is far less than the excellent compounding of the two. It can be seen that the combination of modified bamboo fibers and bentonite can play an excellent compounding synergistic effect. Combining Comparative Examples 4-5 and Table 2, it can be seen that if the quality of modified bamboo fibers is replaced by bamboo fiber raw materials, it is found that the corresponding effects brought by the bamboo fiber raw materials are far less than the excellent modified bamboo fibers, and the combination of bamboo fiber raw materials and bentonite can only bring about a simple superposition of the corresponding effects, and cannot bring about a compounding synergistic effect. Combined with Example 15 and Table 2, it can be seen that when the weight ratio of bentonite to modified bamboo fiber is 0.35:1, the structural stability of the solvent-free anti-corrosion coating during application is better.

[0062] Combining Example 1 and Example 6-7 with Table 2, it can be seen that when the weight ratio of component A to the curing agent is (3-5):1, the coating film formed by the solvent-free anticorrosive coating has excellent structural stability under temperature and pressure changes, and when the weight ratio of bentonite to modified bamboo fiber is 0.35:1, the application effect is better. Combining Examples 16-19 with Table 2, it can be seen that the modified bamboo fiber prepared in the present application can bring stable and excellent corresponding effects after being applied in the solvent-free anticorrosive coating, thereby obtaining a solvent-free anticorrosive coating with better quality.

[0063] Combining Example 1 and Example 8-12 with Table 2, it can be seen that further adding a functional additive obtained by mixing and heating lauric acid and sepiolite powder to the solvent-free anticorrosive coating can significantly reduce the adhesion strength loss rate, indicating that the structural stability of the solvent-free anticorrosive coating is significantly improved when subjected to temperature and pressure changes during application. Combining Example 13-14 with Table 2, it can be seen that if lauric acid and sepiolite powder are used alone, they cannot bring about the excellent effect of the functional additive, indicating that when lauric acid and sepiolite powder are combined under special conditions to form a functional additive, it can bring about a significant improvement effect of 1+1>2.

[0064] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A solvent-free anti-corrosion coating, characterized in that: The method comprises component A and a curing agent in a weight ratio of (3-5):1, wherein component A is made of the following raw materials in parts by weight: Epoxy resin 70-80 parts; Active diluent 15-25 parts; Dispersant 1-5 parts; Pigment 18-20 parts; 20-30 parts of filler; 0.5-1 part of bentonite; 1-3 parts of modified bamboo fiber; The modified bamboo fiber is prepared by the following steps: S1, prepare 2-3 mol / L sodium hydroxide solution, take bamboo fiber raw material and sodium hydroxide solution at (1.4-1.8) g: 1 mL and mix them for 8-10 hours, then take out the bamboo fiber, wash it with deionized water and dry it, to obtain pretreated bamboo fiber; S2, taking anhydrous ethanol, a silane coupling agent and water in a weight ratio of (35-40): (3-5): 1, mixing them to obtain a treatment liquid, and then adding cellulose nanofibers to the treatment liquid, wherein the weight ratio of the cellulose nanofibers to the treatment liquid is 1: (10-12), and mixing to obtain a modified liquid; S3, spray the modified liquid onto the surface of the pretreated bamboo fiber, the spraying amount of the modified liquid is 40-60g / m 2 , and after drying, modified bamboo fiber is obtained.

2. The solvent-free anti-corrosion coating according to claim 1, characterized in that: The diameter of the bamboo fiber raw material is 10-50 μm, and the length is 1-5 mm; the diameter of the cellulose nanofiber is 10-20 nm, and the length is 80-100 nm.

3. The solvent-free anti-corrosion coating according to claim 1, characterized in that: The weight ratio of the bentonite to the modified bamboo fiber is 0.35:

1.

4. The solvent-free anti-corrosion coating according to claim 1, characterized in that: The raw materials of component A are further added with 2-3 parts by weight of a functional additive, which is obtained by mixing sepiolite powder and lauric acid, heating them and then drying them, and the weight ratio of sepiolite powder to lauric acid is 1:(1.6-2).

5. The solvent-free anti-corrosion coating according to claim 4, characterized in that: The weight ratio of the sepiolite powder to lauric acid is 1:1.

8.

6. The solvent-free anti-corrosion coating according to claim 1, characterized in that: The active diluent is one or a combination of allyl glycidyl ether, phenyl glycidyl ether, butyl glycidyl ether, ethylene glycol bisglycidyl ether and resorcinol bisglycidyl ether.

7. The solvent-free anti-corrosion coating according to claim 1, characterized in that: The filler is one or a combination of calcium carbonate, talc powder, wollastonite powder, mica powder, graphite powder and alumina powder.

8. The solvent-free anti-corrosion coating according to claim 1, characterized in that: The curing agent is alicyclic amine resin Baxxodur EC330.

9. The solvent-free anti-corrosion coating according to claim 1, characterized in that: The weight ratio of the A component to the curing agent is 4:

1.

10. The method for preparing the solvent-free anticorrosive coating according to claim 1, characterized in that: The following steps are involved: (1) Prepare raw materials including epoxy resin, active diluent, dispersant, pigment, filler, bentonite, modified bamboo fiber and curing agent according to the proportion; (2) stirring the epoxy resin in step (1) at 300-700 r / min, then adding active diluent, dispersant, pigment, filler, bentonite and modified bamboo fiber during stirring, stirring at 1000-1200 r / min for 15-20 min after the addition, and then grinding to obtain component A; (3) Component A and the curing agent are stirred and mixed according to the usage ratio to obtain a solvent-free anti-corrosion coating.

Citation Information

Patent Citations

  • Underwater solventless epoxy anti-corrosive coating and preparation method thereof

    CN101619189A

  • Heat-insulation energy-saving material for building and preparation method of heat-insulation energy-saving material

    CN117924957A

  • Solvent-free electrostatic conductive paint and preparation method therefor

    WO2015100583A1